Analisis Perawatan Mesin Aftertreatment Menggunakan Metode Overall Equipment Effectiveness (Oee) Dan Six Big Losses Untuk Meningkatkan Efektifitas Mesin Pada PT. XYZ - Muhammad Ali Akbar; Dzikry Lukman; Bintang Nidia Kusuma (Jurnal Teknologika, 2025)
This study aims to analyze the effectiveness of the AfterTreatment machine maintenance at PT XYZ using the Overall Equipment Effectiveness (OEE) and Six Big Losses methods. The AfterTreatment machine is a crucial part of the rayon fiber production process but has been experiencing a high level of downtime. The OEE method is used to measure machine effectiveness based on three key components: availability, performance efficiency, and quality. Data was collected from machine operations between September 2024 and February 2025. The results show that the average OEE value is 75.99%, which is below the world-class standard of 85%. The primary causes of low OEE are losses due to reduced speed, equipment failure, and idling & minor stoppages. By identifying the loss causes through the Six Big Losses and Fishbone Diagram methods, this research proposes improvements including preventive maintenance planning and enhanced operator training. The study concludes that machine effectiveness can be improved by minimizing major losses and optimizing maintenance strategies.